The Crucial Role of Carbohydrate Intake for Female Long-Distance Runners : A Literature Review - Reza Restu Illahi; Willadi Rasyid; Hendri Neldi; Padli Padli; Yovhandra Ockta; Firunika Intan Cahyani (Jurnal Penelitian Pendidikan IPA, 2023)
This research is a literature study that aims to explore the relationship between carbohydrate consumption and athlete performance and health, especially female athletes who run long distances. This study uses the method of literature study or literature review using secondary data from scientific journal articles. Article searches are conducted through various platforms such as Google Scholar, EBSCO, ScienceDirect, and Proquest using keywords related to carbohydrate consumption in female long-distance runners. The inclusion criterion for articles is that they must be scientific journal research articles conducted in the UK with the main subject female athletes long-distance runners and the topic relates to carbohydrates. Articles that meet these criteria are then further analyzed Through an analysis of 8 scientific journal articles, it was concluded that carbohydrate intake has a crucial role in improving athletes' performance and endurance, as well as preventing the risk of low energy availability that can have a negative impact on health. In addition, research also highlights the need for adjustments in carbohydrate intake based on environment and stress to maximize athletes' training and recovery abilities. These findings affirm the importance of designing a balanced diet of carbohydrates and protein to achieve the desired results in improving athlete performance and supporting healthy weight loss. This study provides a deep understanding of the importance of carbohydrate intake in supporting the performance and health of female long-distance runners, and emphasizes the need for more inclusive research to develop better nutritional interventions.